Significance of ST‐Segment elevation in V4R lead in patients with anterior myocardial infarction. Issue 5 (5th June 2021) - Dehghani, Pooyan; Zahedi, Ali; Hassanzadeh, Mani; Alavi, Seyed Hosein; Jannati, Mansour; Mehdipour Namdar, Zahra; Aslani, Amir
Abstract: Background: There is some evidence of the association between ST‐segment elevation in the V4R chest lead and the likelihood of anterior wall myocardial infarction; however, the link of this phenomenon with the location and the severity of the coronary involvements in such patients remains uncertain. We aimed to investigate the ST‐segment elevation in V4R leads in patients with anterior myocardial infarction and also its effect on prognosis as well as the detection and prediction of the location of arterial stenosis in coronary angiography. Methods: Data collection was performed by reviewing the hospital recorded files of 195 patients' suspicion of acute myocardial infarction who have been referred within 2 h of the onset of cardiac symptoms. The patients were then categorized into two groups with and without ST elevation in the V4R chest lead. Results: Comparing two groups showed a significantly higher rate of concurrent ST‐segment elevation in V1 lead in those with ST‐segment elevation in V4R. Echocardiography on the day after anterior myocardial infarction showed LVEF <40% in 74% and 35.2% of patients with and without ST‐segment elevation in V4R, respectively, indicating a significant difference. The lesions on proximal LAD were more common in the group with ST‐segment elevation in V4R. Conclusion: Our study emphasized a high likelihood of ST‐segment elevation in V4R lead concurrently with ST‐elevation in V1 lead. Also, the appearance of ST‐segment elevation in V4R lead can be accompanied with a lower LVEF, myocardial infarct size, involvement of proximal part of LAD, and Wrap around LAD.